Genome-wide DNA methylation profiling of the regenerative MRL/MpJ mouse and two normal strains. (August 2017) - Górnikiewicz, Bartosz; Ronowicz, Anna; Madanecki, Piotr; Sachadyn, Paweł
Aim: We aimed to identify the pivotal differences in the DNA methylation profiles between the regeneration capable MRL/MpJ mouse and reference mouse strains.Materials & methods: Global DNA methylation profiling was performed in ear pinnae, bone marrow, spleen, liver and heart from uninjured adult females of the MRL/MpJ and C57BL/6J and BALB/c.Results & conclusion: A number of differentially methylated regions (DMRs) distinguishing between the MRL/MpJ mouse and both references were identified. In the ear pinnae, the DMRs were enriched in genes associated with development, inflammation and apoptosis, and in binding sites of transcriptional modulator Smad1. Several DMRs overlapped previously mapped quantitative trait loci of regenerative capability. The results suggest potential epigenetic determinants of regenerative phenomenon.